Absorbent and sanitary products
By using alternating coating and bonding of nonwoven fabrics and superabsorbent layers in sanitary products, the problems of unstable fixation of superabsorbent particles and difficulty in thinning of products are solved, and the effects of high-performance absorption and cost reduction are achieved.
Patent Information
- Application Number
- JP2024546004
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-11-16
- Filing Date
- 2023-11-16
- Publication Date
- 2025-02-06
- Estimated Expiration
- 2043-11-16
AI Technical Summary
The use of wood pulp fibers (pulp) in existing sanitary products makes it difficult to thin the product, and the superabsorbent particles are fixed and unstable, affecting the absorption performance and wear comfort, while increasing production costs.
The alternating coating and bonding between the nonwoven fabric and the superabsorbent layer is adopted to fix the superabsorbent particles through the adhesive, avoid the use of wood pulp fibers, and ensure the stable distribution of the superabsorbent in sanitary products and high filling rate.
It realizes thinning and high-performance absorption of sanitary products, while reducing production costs and improving wearable comfort and absorption uniformity.
Smart Images

Figure 2025504102000001_ABST
Abstract
Description
[Technical field]
[0001] [CROSS REFERENCE TO RELATED APPLICATIONS] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0153919 dated November 16, 2022 and Korean Patent Application No. 10-2023-0159226 dated November 16, 2023, and all contents disclosed in the documents of said Korean patent applications are incorporated herein by reference.
[0002] The present invention relates to an absorbent body and a sanitary product that can contribute to making the absorbent body and the sanitary product thinner by appropriately fixing highly absorbent resin particles in the absorbent body and the sanitary product without using pulp, and that exhibits excellent shape retention even after absorbing moisture, and a sanitary product containing the absorbent body. [Background technology]
[0003] Generally, sanitary products such as various diapers, sanitary napkins, and incontinence pads contain absorbents containing super absorbent polymer particles. Such absorbents generally contain the super absorbent polymer particles and pulp to properly fix the super absorbent polymer particles while maintaining the shape of the absorbent and the sanitary product.
[0004] However, the presence of such pulp makes it difficult to make the absorbent and sanitary products slimmer and thinner, and causes problems such as sweat accumulating between the user's skin and the sanitary products, resulting in poor comfort when worn. Moreover, it is necessary to use a large amount of the pulp, which is mainly obtained from wood, which goes against the recent trend toward environmental protection and is in fact one of the main causes of increasing the manufacturing costs of the absorbent and sanitary products.
[0005] Therefore, many attempts have been made to reduce the amount of pulp used in the absorbent layers and sanitary products, or to provide sanitary products such as so-called pulpless diapers that do not use pulp.
[0006] However, when the amount of the pulp used is reduced too much, the binding strength is low, causing multiple breaks in the absorbent body, and further, since the superabsorbent resin particles are not properly fixed in the absorbent body and the sanitary product, the absorbent body moves to a specific location during transportation of the sanitary product, causing uneven absorption performance, and the shape of the sanitary product cannot be properly maintained.
[0007] Meanwhile, in conventional sanitary products that do not use pulp, such as pulpless diapers, the superabsorbent resin particles are fixed mainly using a liquid adhesive composition instead of pulp, thereby attempting to make the absorbent and sanitary products thinner and slimmer, and to realize low unit prices by not using pulp. However, in conventional sanitary products, when an excessive amount of adhesive is used, there are disadvantages such as the adhesive reducing the performance of the superabsorbent resin particles and the absorbent itself that contains them, or the adhesive moving causing process troubles.
[0008] Conversely, when the amount of adhesive used is reduced, there is a disadvantage that the superabsorbent resin particles are not properly fixed in the absorbent body and sanitary goods, resulting in uneven absorption performance due to particle movement, etc. In addition, the problem that the shape of the absorbent body and sanitary goods cannot be properly maintained after the superabsorbent resin particles absorb water remains unresolved.
[0009] Due to these problems with the conventional technology, there is a continuing demand for technological development related to absorbents and sanitary products that do not use fluff pulp or use a significantly reduced amount of fluff pulp while still being able to properly fix highly absorbent resin particles within the absorbent and sanitary products without a decrease in performance, and that exhibit excellent shape retention even after absorbing moisture. Summary of the Invention [Problem to be solved by the invention]
[0010] The present invention relates to an absorbent body that can contribute to making absorbent bodies and sanitary products thinner by appropriately fixing highly water-absorbent resin particles therein without using pulp, and that exhibits excellent shape retention even after absorbing moisture.
[0011] The present invention also relates to a sanitary article comprising said absorbent body. [Means for solving the problem]
[0012] In order to solve the above problems, the present invention provides A first nonwoven fabric; A second nonwoven fabric; A superabsorbent polymer layer is provided between the first and second nonwoven fabrics. the superabsorbent polymer layer is bonded to the first and second nonwoven fabrics via an adhesive, does not contain pulp, Satisfy the following (1) and (2); Absorber.
[0013] (1) The absorbent body is vibrated 100 times at a frequency of 65 times / min and an amplitude of 15 mm, and the fixation rate is measured to measure the amount of superabsorbent polymer remaining in the absorbent body without leakage, and is 90% or more; (2) The absorbent material is dyed with a dye and then dried. After confirming that only the highly absorbent resin portion is selectively dyed, the area of the dyed portion is measured with a color meter to determine a filling rate of 90% or more.
[0014] The present invention also provides a sanitary product comprising the absorbent body. Effect of the Invention
[0015] According to the present invention, an absorbent body having excellent shape retention even after absorbing water and excellent absorption performance is provided without using pulp by appropriately fixing a superabsorbent polymer. Since the absorbent body does not use pulp, it can have a slim and thin structure and the manufacturing cost can be reduced.
[0016] Therefore, the present invention can contribute to making sanitary products such as diapers slimmer, thinner, and more functional, improving the wearing comfort, and also significantly reducing the manufacturing cost. [Brief description of the drawings]
[0017] [Figure 1] 1 relates to the cross section of the absorbent body of Examples 1 to 3, and shows an absorbent body in which a first nonwoven fabric 1, an adhesive layer 3, a first coated layer of superabsorbent polymer 4, a first coated layer of adhesive 5, a second coated layer of superabsorbent polymer 6, a second coated layer of adhesive 7, a third coated layer of superabsorbent polymer 8, an adhesive layer 9, and a second nonwoven fabric 2 are laminated in this order. The layers 4 to 8 are superabsorbent polymer layers. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The terms used in this specification are merely used to describe exemplary embodiments and are not intended to limit the present invention. A singular expression includes a plural expression unless the context clearly indicates otherwise. In this specification, the terms "include", "comprise", "have" and the like are intended to specify the presence of an implemented feature, step, component, or combination thereof, and should be understood not to preclude the presence or additional possibility of one or more other features, steps, components, or combinations thereof.
[0019] Since the present invention can be modified in various ways and can have various forms, specific embodiments are illustrated and described in detail below, but it is not intended to limit the present invention to the specific disclosed forms, and it should be understood that the present invention includes all modifications, equivalents, and alternatives falling within the spirit and technical scope of the present invention.
[0020] In addition, the terminology used in this specification is merely for the purpose of referring to specific embodiments and is not intended to limit the present invention. Additionally, the singular forms used herein include the plural forms unless the context clearly indicates otherwise.
[0021] In the present invention, terms such as first, second, third, etc. are used to describe various components, and the terms are used only for the purpose of distinguishing one component from another component.
[0022] The term "polymer" or "polymeric polymer" used in the present specification means a state in which an acrylic acid monomer, which is a water-soluble ethylenically unsaturated monomer, is polymerized, and can include any range of water content or particle size. Among the above polymers, a polymer in a state after polymerization and before drying and having a water content (water content) of about 40% by weight or more can be called a hydrogel polymer, and particles obtained by crushing and drying such a hydrogel polymer can be called a crosslinked polymer.
[0023] In addition, the term "superabsorbent resin particles" refers to a particulate material including a crosslinked polymer obtained by polymerizing an acrylic acid monomer having acidic groups and at least a portion of the acidic groups being neutralized, and crosslinking the polymer with an internal crosslinking agent.
[0024] In addition, the term "super absorbent polymer" refers to a crosslinked polymer obtained by polymerizing an acrylic acid monomer containing acidic groups and at least a portion of the acidic groups being neutralized, or a powder-like base resin made of super absorbent polymer particles obtained by pulverizing the crosslinked polymer, depending on the context, or is used to encompass the crosslinked polymer or base resin that has been subjected to additional processes, such as surface crosslinking, regranulation into fine powder, drying, pulverization, classification, etc., to be in a state suitable for commercialization. Thus, the term "super absorbent polymer" can be interpreted as including a plurality of super absorbent polymer particles.
[0025] As the demand for thin and light diapers increases, research is being conducted into pulpless diapers, which do not contain pulp. In pulpless diapers, the superabsorbent polymer (SAP) must be fixed in the absorbent body of the diaper even when the pulp is removed.
[0026] Therefore, the inventors of the present invention confirmed that it is possible to obtain excellent shape retention and absorption performance of the absorbent body by applying the adhesive and superabsorbent polymer successively multiple times without using pulp, while increasing the fixation rate of the superabsorbent polymer by applying the superabsorbent polymer uniformly inside the absorbent body to improve the filling rate, and thus completed the present invention.
[0027] The absorbent body and the sanitary article will be described in more detail below with reference to specific embodiments of the invention.
[0028] Absorber An absorbent body according to one embodiment of the present invention includes a first nonwoven fabric, a second nonwoven fabric, and a superabsorbent polymer layer between the first and second nonwoven fabrics, the superabsorbent polymer layer being bonded to the first and second nonwoven fabrics via an adhesive, not including pulp, and satisfying the following (1) and (2):
[0029] (1) The absorbent body is vibrated 100 times at a frequency of 65 times / min and an amplitude of 15 mm, and the amount of superabsorbent polymer remaining in the absorbent body without leakage is measured, and the fixation rate is 90% or more; (2) The absorbent material is dyed with a dye and then dried. After confirming that only the highly absorbent resin portion is selectively dyed, the area of the dyed portion is measured with a color meter to determine a filling rate of 90% or more.
[0030] Specifically, the absorbent does not contain pulp, but the superabsorbent polymer and adhesive are alternately applied two or more times, so that the superabsorbent polymer can be more firmly fixed inside the absorbent, and the above structure can increase the packing rate of the superabsorbent polymer inside the absorbent. Therefore, when the absorbent of one embodiment is applied, the movement of the superabsorbent polymer particles is suppressed without using pulp, so that the absorbent and sanitary products can exhibit uniform absorption performance, which can greatly contribute to making the absorbent and sanitary products containing the same thinner, slimmer, and more cost-effective.
[0031] At the same time, by adopting a structure in which the adhesive is applied alternately, the highly water-absorbent resin particles can be stably positioned even if less adhesive composition is used than before, and the fixing rate and filling rate are improved, eliminating the risk of a decrease in the physical properties of the highly water-absorbent resin particles that occurs when a large amount of adhesive composition is used.
[0032] Therefore, it has been confirmed that the absorbent of one embodiment not only solves the problems of known sanitary products that do not use pulp, such as pulpless diapers, but also exhibits excellent performance, shape retention and wearing comfort, and can greatly contribute to making sanitary products thinner and slimmer.
[0033] In the absorbent of the embodiment, the nonwoven fabric is not particularly limited as long as it is a nonwoven fabric generally used in absorbents. For example, the nonwoven fabric may be a polypropylene-based nonwoven fabric, a polyethylene-based nonwoven fabric, a polyolefin-based multi-component nonwoven fabric (e.g., a PE / PP bicomponent nonwoven fabric layer), a PLA (Poly lactic acid) / PBS (Poly Butyl Succinate) material nonwoven fabric, or other various materials. Each of these nonwoven fabrics can be directly manufactured by a conventional nonwoven fabric manufacturing method or can be commercially obtained and used, so further description thereof will be omitted.
[0034] Preferably, the nonwoven fabric does not include nap. The "napping" is a method of scraping or pulling out fibers to raise nap on the surface of the fabric, and is not particularly limited as long as it corresponds to a fabric manufactured by a normal nap manufacturing method. When the nonwoven fabric includes nap and the superabsorbent polymer is supported between the naps, the fixation rate of the supported superabsorbent polymer may decrease. This is because, in a form in which the superabsorbent polymer is supported between the naps, the fixation of the superabsorbent polymer depends only on adsorption with the nap, and there is a limit to fixation of the superabsorbent polymer by the adsorption alone.
[0035] The superabsorbent polymer layer is formed by alternately applying and laminating the superabsorbent polymer and the adhesive, and may be alternately applied preferably 2 or more times, or 3 or more times, and 10 or less times, 8 or less times, 6 or less times, or 5 or less times. In addition, since the superabsorbent polymer layer is bonded to the nonwoven fabric via the adhesive, preferably the top and bottom layers of the superabsorbent polymer layer are coated with the superabsorbent polymer.
[0036] More preferably, the superabsorbent resin layer may be formed by sequentially laminating a first coating layer of superabsorbent resin, a first coating layer of adhesive, a second coating layer of superabsorbent resin, a second coating layer of adhesive, and a third coating layer of superabsorbent resin.
[0037] Preferably, the thickness of the superabsorbent polymer layer may be 5 mm or less, 4 mm or less, or 3 mm or less. The thinner the thickness of the superabsorbent polymer layer, the better the wearing comfort, but as an example, the thickness may be 1 mm or more. If the thickness of the superabsorbent polymer layer exceeds 5 mm, there is a problem that it becomes difficult to make the sanitary product thin and slim.
[0038] Preferably, the highly water-absorbent polymer layer has a surface area of 100 mm. 2 The superabsorbent polymer layer may contain 100 g or more per unit area (m). Preferably, the superabsorbent polymer layer may contain 110 g or more, 120 g or more, 130 g or more, 140 g or more, or 150 g or more, and 300 g or less, 250 g or less, 240 g or less, 230 g or less, 220 g or less, 210 g or less, or 200 g or less. 2 If the content of superabsorbent polymer per unit area (m2) is less than 100g, the absolute amount of superabsorbent polymer may be insufficient, resulting in a decrease in absorption performance. 2 If the content of superabsorbent polymer exceeds 300 g per unit area, the volume of the superabsorbent polymer layer increases, making it difficult to make the absorbent body thinner and slimmer.
[0039] On the other hand, the absorbent body is vibrated 100 times at a frequency of 65 times / min and an amplitude of 15 mm, and the amount of superabsorbent polymer remaining in the absorbent body without leakage is measured to have a fixation rate of 90% or more. Preferably, the fixation rate may be 95% or more, 97% or more, 98% or more, 99% or more, or 99.1% or more, or may be 100% or less.
[0040] The absorbent body is dyed with a dye and then dried, and after confirming that only the highly absorbent resin portion is selectively dyed, the area of the dyed portion is measured with a color meter to have a filling rate of 90% or more. Preferably, the filling rate is 95% or more, 97% or more, 98% or more, 99% or more, or 99.5% or more, or may be 100% or less.
[0041] On the other hand, the highly water-absorbent resin contained in the absorbent body of the present invention is as follows.
[0042] The superabsorbent resin includes a base resin including a crosslinked polymer of an acrylic acid monomer in which at least a portion of the acidic groups have been neutralized and an internal crosslinking agent, and a surface crosslinked layer formed on the base resin and in which the crosslinked polymer is additionally crosslinked via a surface crosslinking agent.
[0043] The superabsorbent polymer may have a water retention capacity (CRC) of 32 g / g to 40 g / g as measured by EDANA NWSP 241.0.R2(15). Preferably, the water retention capacity of the superabsorbent polymer may be 32 g / g or more, 33 g / g or more, or 33.4 g / g or more, and 40 g / g or less, 39 g / g or less, or 38.7 g / g or less. If the water retention capacity of the superabsorbent polymer is less than 32 g / g, there is a problem that the rewetting performance and absorbency are reduced, and if the water retention capacity of the superabsorbent polymer is more than 40 g / g, there is a problem that not only is it difficult to manufacture the superabsorbent polymer, but also the pressurization performance is reduced, resulting in a reduced rewetting property.
[0044] The superabsorbent polymer may have a water soluble content of 10% by weight or less after swelling for 16 hours as measured according to EDANA NWSP 270.0.R2(15).Preferably, the water soluble content of the superabsorbent polymer after swelling for 16 hours may be 9% by weight or less, 8% by weight or less, or 7.7% by weight or less, and 1% by weight or more, 3% by weight or more, or 5% by weight or more.
[0045] The superabsorbent polymer may have an absorption speed (vortex time) of 30 seconds or less by the vortex method. Preferably, it may be 29 seconds or less or 28 seconds or less. The smaller the value of the absorption speed, the better. The lower limit of the absorption speed is theoretically 0 seconds, but may be, for example, 10 seconds or more, 15 seconds or more, 18 seconds or more, 20 seconds or more, 21 seconds or more, or 22 seconds or more. If the absorption speed of the superabsorbent polymer exceeds 30 seconds, there is a problem that the rewetting performance is also reduced. A superabsorbent polymer having an absorption speed of less than 10 seconds is not only difficult to manufacture, but also difficult to diffuse inside the diaper during the manufacture of the diaper, so that it is absorbed locally, and the core may break or aggregate. At this time, the method for measuring the absorption speed of the superabsorbent polymer will be described in more detail in the experimental examples described below.
[0046] The superabsorbent polymer may have a bulk density, as measured by EDANA NWSP 251.0.R2(15), of 0.55 g / ml or more and 0.65 g / ml or less. Preferably, the bulk density of the superabsorbent polymer may be 0.56 g / ml or more, 0.57 g / ml or more, or 0.58 g / ml or more, and 0.63 g / ml or less, 0.62 g / ml or less, or 0.60 g / ml or less.
[0047] Since the same weight of superabsorbent polymer is used when manufacturing diapers, if the bulk density is less than 0.55 g / ml, the volume of the superabsorbent polymer increases and gel blocking may occur, and if it exceeds 0.65 g / ml, the particle volume per same weight decreases and the absorption rate may decrease.
[0048] Meanwhile, the acrylic acid monomer is a compound represented by the following Chemical Formula 1.
[0049] [Chemical formula 1] R 1 -COOM 1
[0050] In the above Chemical Formula 1, R 1 is an alkyl group having 2 to 5 carbon atoms and containing an unsaturated bond, M 1 is a hydrogen atom, a monovalent or divalent metal, an ammonium group, or an organic amine salt.
[0051] Preferably, the acrylic acid monomer includes at least one selected from the group consisting of acrylic acid, methacrylic acid, and their monovalent metal salts, divalent metal salts, ammonium salts, and organic amine salts.
[0052] Here, the acrylic acid monomer may have an acidic group, and at least a part of the acidic group may be neutralized. Preferably, the monomer may be partially neutralized with an alkaline material such as sodium hydroxide, potassium hydroxide, or ammonium hydroxide. In this case, the neutralization degree of the acrylic acid monomer may be 40 to 95 mol%, 40 to 80 mol%, or 45 to 75 mol%. The range of the neutralization degree may be adjusted according to the final physical properties. However, if the neutralization degree is too high, the neutralized monomer may precipitate and the polymerization may not proceed smoothly. Conversely, if the neutralization degree is too low, the absorbency of the polymer may be significantly reduced and the polymer may exhibit properties similar to elastic rubber, which is difficult to handle.
[0053] The concentration of the acrylic acid monomer may be about 20 to about 60% by weight, preferably about 40 to about 50% by weight, based on the monomer composition including the raw material of the superabsorbent polymer and the solvent, and may be an appropriate concentration taking into consideration the polymerization time and reaction conditions, etc. However, if the concentration of the monomer is too low, the yield of the superabsorbent polymer may be low, which may cause problems in terms of economy, and conversely, if the concentration is too high, a part of the monomer may be precipitated, or the crushing efficiency may be low when crushing the polymerized hydrogel polymer, which may cause problems in the process, and the physical properties of the superabsorbent polymer may be deteriorated.
[0054] In addition, the term "internal crosslinking agent" used in this specification is a term used to distinguish it from a surface crosslinking agent for crosslinking the surface of superabsorbent resin particles described later, and plays a role in crosslinking and polymerizing the unsaturated bonds of the water-soluble ethylenically unsaturated monomer described above. The crosslinking in the above step is performed without distinction between the surface and the inside, but when the surface crosslinking process of the superabsorbent resin particles described later is performed, the particle surface of the finally manufactured superabsorbent resin has a structure crosslinked by the surface crosslinking agent, and the inside has a structure crosslinked by the internal crosslinking agent.
[0055] As the internal crosslinking agent, any compound can be used as long as it allows the introduction of crosslinking bonds during polymerization of the acrylic unsaturated monomer. Specifically, as the internal crosslinking agent, a crosslinking agent having one or more functional groups capable of reacting with the water-soluble substituent of the acrylic unsaturated monomer and having one or more ethylenically unsaturated groups; or a crosslinking agent having two or more functional groups capable of reacting with the water-soluble substituent of the monomer and / or the water-soluble substituent formed by hydrolysis of the monomer can be used. As an example, the internal crosslinking agent may be an epoxy compound.
[0056] As the internal crosslinking agent, any compound can be used as long as it can introduce crosslinking during polymerization of the acrylic acid-based unsaturated monomer.Specifically, as the internal crosslinking agent, a crosslinking agent having one or more functional groups that can react with the water-soluble substituent of the acrylic acid-based unsaturated monomer and having one or more ethylenic unsaturated groups; or a crosslinking agent having two or more functional groups that can react with the water-soluble substituent of the monomer and / or the water-soluble substituent formed by the hydrolysis of the monomer can be used.
[0057] The internal crosslinking agent may be an epoxy compound or a polyethylene glycol-based polymer. Non-limiting examples of the internal crosslinking agent include N,N'-methylenebisacrylamide, trimethylpropane tri(meth)acrylate, ethylene glycol di(meth)acrylate, polyethylene glycol (meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, polypropylene glycol (meth)acrylate, butanediol di(meth)acrylate, butylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, hexanediol di(meth)acrylate, triethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, dipentaerythritol pentaacrylate, and glycerin tri(meth)acrylate. Examples of the crosslinking agent include, but are not limited to, acrylate-based compounds such as acrylate and pentaerythritol tetraacrylate; epoxy-based compounds such as ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, tripropylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, polytetramethylene glycol diglycidyl ether, glycerol diglycidyl ether, glycerol triglycidyl ether, diglycerol polyglycidyl ether, and polyglycerol polyglycidyl ether; triarylamines; propylene glycol; glycerin; and polyfunctional crosslinking agents such as ethylene carbonate, which may be used alone or in combination of two or more.
[0058] According to an embodiment, the internal crosslinking agent may be an epoxy-based compound. For example, the internal crosslinking agent may be a polyfunctional epoxy compound having a valence of 2 or more, such as ethylene glycol diglycidyl ether. In this case, the foaming agent may be stably foamed by the hydrophobic particles.
[0059] In the monomer composition, the internal crosslinking agent can be used in an amount of 0.01 to 5 parts by weight based on 100 parts by weight of the acrylic acid monomer. For example, the internal crosslinking agent can be used in an amount of 0.01 parts by weight or more, 0.05 parts by weight or more, 0.1 parts by weight or more, or 0.15 parts by weight or more, and 5 parts by weight or less, 3 parts by weight or less, 2 parts by weight or less, 1 part by weight or less, or 0.7 parts by weight or less based on 100 parts by weight of the water-soluble ethylenically unsaturated monomer. If the content of the internal crosslinking agent is too low, crosslinking does not occur sufficiently, so it may be difficult to achieve strength above an appropriate level, and if the content of the internal crosslinking agent is too high, the internal crosslinking density may be high, so it may be difficult to achieve the desired water retention ability.
[0060] The crosslinking polymerization of the water-soluble ethylenically unsaturated monomer in the presence of such an internal crosslinking agent may be carried out by thermal polymerization, photopolymerization or hybrid polymerization in the presence of a polymerization initiator and, if necessary, a thickener, a plasticizer, a storage stabilizer, an antioxidant, etc., the details of which will be described later.
[0061] In addition, the superabsorbent resin further includes a surface cross-linked layer formed by additionally cross-linking the cross-linked polymer contained in the base resin via a surface cross-linking agent on at least a part of the surface of the base resin, in order to increase the surface cross-linking density of the superabsorbent resin. When the superabsorbent resin further includes a surface cross-linked layer as described above, the superabsorbent resin has a structure in which the cross-linking density is higher on the outside than on the inside.
[0062] As the surface cross-linking agent, any surface cross-linking agent that has been used in the manufacture of a superabsorbent resin can be used without any particular limitation. For example, the surface cross-linking agent may include one or more selected from the group consisting of polyhydric alcohol compounds, polyfunctional epoxy compounds, polyamine compounds, haloepoxy compounds, condensation products of haloepoxy compounds, oxazoline compounds, and alkylene carbonate compounds.
[0063] Specifically, examples of the polyhydric alcohol compound that can be used include mono-, di-, tri-, tetra- or polyethylene glycol, monopropylene glycol, 1,3-propanediol, dipropylene glycol, 2,3,4-trimethyl-1,3-pentanediol, polypropylene glycol, glycerol, polyglycerol, 2-butene-1,4-diol, 1,4-butanediol, 1,3-butanediol, 1,5-pentanediol, 1,6-hexanediol, and 1,2-cyclohexanedimethanol.
[0064] As the polyfunctional epoxy compound, ethylene glycol diglycidyl ether, glycidol, or the like can be used.
[0065] The polyamine compound may be ethylenediamine, diethylenetriamine, triethylenetetraamine, tetraethylenepentamine, pentaethylenehexamine, polyethyleneimine, polyamidepolyamine, or the like.
[0066] As the haloepoxy compound, epichlorohydrin, epibromohydrin, α-methylepichlorohydrin, or the like can be used.
[0067] As the oxazoline-based compound, mono-, di- or polyoxazolidinones can be used.
[0068] As the alkylene carbonate compound, ethylene carbonate, propylene carbonate, glycerol carbonate, or the like can be used.
[0069] More specifically, the surface cross-linking agent may be one of the above-mentioned surface cross-linking agents, or may be used in combination with one another. As an example, an alkylene carbonate compound such as ethylene carbonate may be used as the surface cross-linking agent.
[0070] Meanwhile, the superabsorbent polymer may contain 10% by weight or less of particles having a particle size of 710 μm or more and 850 μm or less. Also, the superabsorbent polymer may contain 10% by weight or less of particles having a particle size of 150 μm or less. The particle size of the superabsorbent polymer particles may be measured according to the European Disposables and Nonwovens Association (EDANA) standard EDANA WSP 220.3 method.
[0071] If the content of particles having a particle size of 710 μm to 850 μm is high and exceeds 10% by weight, the thin pulpless diaper generally feels hard and may have tactile problems such as poor wearing comfort, and the absorption rate is also reduced. Also, if the content of particles having a particle size of 150 μm or less exceeds 10% by weight, there is a possibility that a problem of clogging of the filter during processing may occur due to a large amount of fine powder, and there is also a disadvantage that the working environment becomes poor.
[0072] On the other hand, the rewet value measured for an absorbent material containing the superabsorbent polymer may be 3 g or less. Preferably, the rewet value may be 1 g or more, 1.5 g or more, 2.0 g or more, or 2.4 g or more, and 3 g or less, 2.9 g or less, or 2.7 g or less.
[0073] The rewet value can be measured from the absorbent. 85 mL of 0.9 wt % sodium chloride aqueous solution (physiological saline) is poured into the center of the absorbent (350 mm x 100 mm in size), and after 2 minutes, a paper (300 gsm filter paper) with a size of 300 mm x 90 mm is placed on the absorbent. After 2 minutes, the amount of saltwater that has seeped out from the absorbent into the paper is measured, and the paper is removed. 15 minutes after the injection of the physiological saline, a weight is placed on the absorbent and a pressure of 0.42 psi is applied, while another 85 mL of physiological saline is poured into the same position. After 15 minutes, the weight placed on the absorbent is removed for a while, and a new paper is placed on the absorbent, and the weight is placed on the paper again to position the paper between the absorbent and the weight. After 2 minutes, the amount of saltwater that has seeped out from the absorbent into the paper is measured, and the rewet amount (g) is calculated according to the following mathematical formula 3.
[0074] [Mathematical formula 3] Rewetting amount (g)=(W5(g)-W6(g))+(W7(g)-W6(g))
[0075] In the above mathematical formula 3, W5(g) is the weight of the paper that absorbs the liquid that seeps out from the absorbent body for 2 minutes 2 minutes after saline solution is injected into the absorbent body under no pressure, W6(g) is the initial weight of the paper, and W7(g) is the weight of the paper that absorbs the liquid that seeps out from the absorbent sheet for 2 minutes under a load (0.42 psi) after saline solution is injected into the absorbent sheet under no pressure and under pressure.
[0076] The superabsorbent resin may also include hydrophobic particles. Here, hydrophobic particles refer to water-insoluble particles that have a contact angle with water of 50° or more or that do not dissolve in water. Particles with a contact angle with water of less than 50° and water-soluble particles can be dissolved in the monomer composition in the form of an aqueous solution and are unlikely to capture bubbles generated during the polymerization process, whereas hydrophobic particles are located at the interface between bubbles of carbon dioxide or the like that exhibit hydrophobicity inside the neutralization liquid and the neutralization liquid, and can effectively capture and stabilize the bubbles.
[0077] Therefore, the hydrophobic particles have a contact angle with water of 50° or more. More specifically, the hydrophobic particles may have a contact angle with water of 70° or more, 100° or more, 120° or more, or 130° or more, and 175° or less.
[0078] At this time, the contact angle of the hydrophobic particles may be measured by the following method. First, a coating solution is prepared by dispersing the hydrophobic particles in a methylene chloride solvent at a concentration of 5 wt %. Then, the coating solution is spin-coated on a wafer having no surface roughness, and the wafer is dried at room temperature to remove the remaining solvent. Then, water is dropwise dropped on the coating layer to measure the contact angle, which is defined as the contact angle of each hydrophobic particle.
[0079] In addition, the hydrophobic particles have an average particle size of 0.2 μm to 50 μm, but if the average particle size of the hydrophobic particles is less than 0.2 μm, it is difficult to effectively capture bubbles generated during the manufacturing process, so that uniform pores cannot be formed, and if the average particle size of the hydrophobic particles exceeds 50 μm, the size of the pores formed may be too large, so that it is difficult to improve the absorption rate of the superabsorbent resin. Specifically, for example, the hydrophobic particles may have an average particle size (μm) of 0.3 or more, 0.5 or more, 1 or more, 2 or more, or 3 or more, and 40 or less, 35 or less, or 30 or less.
[0080] Here, the average particle size of the hydrophobic particles means D50, and the "particle size Dn" means the particle size at n% of the particle number cumulative distribution by particle size. That is, D50 is the particle size at 50% of the particle number cumulative distribution by particle size, D90 is the particle size at 90% of the particle number cumulative distribution by particle size, and D10 is the particle size at 10% of the particle number cumulative distribution by particle size. The Dn can be measured using a laser diffraction method. Specifically, the powder to be measured is dispersed in a dispersion medium, and then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500). When the particles pass through a laser beam, the difference in the diffraction pattern according to the particle size is measured to calculate the particle size distribution. D10, D50, and D90 can be measured by calculating the particle diameter at 10%, 50%, and 90% of the particle number cumulative distribution by particle size in the measuring device.
[0081] Such hydrophobic particles may be one or more selected from the group consisting of hydrophobic silica, metal salts of fatty acids having 7 to 24 carbon atoms, and hydrophobic organic particles.
[0082] Here, hydrophobic silica is a general term for silica that has a low content of silanol (-SiOH) on the surface and therefore has a contact angle with water of 50° or more, and any hydrophobic silica known in the art can be used without limitation.
[0083] In addition, the metal salt of a fatty acid having 7 to 24 carbon atoms refers to a compound in which a metal cation is bonded instead of a hydrogen ion of a carboxyl group at the end of an unsaturated or saturated fatty acid having a linear structure and a carbon number of 7 to 24 in the molecule, and in this case, the metal salt may be a monovalent metal salt or a polyvalent metal salt having a valence of 2 or more. In this case, when the hydrophobic particles are metal salts of fatty acids having less than 7 carbon atoms, it is not possible to capture air bubbles that are ionized in an aqueous solution and generated in the form of particles, and when the hydrophobic particles are metal salts of fatty acids having more than 24 carbon atoms, the fatty acid chains become long and dispersion may be difficult.
[0084] Specifically, when the metal salt of the fatty acid is a monovalent metal salt, it has a structure in which one fatty acid carboxylate anion is bound to an alkali ion, which is a monovalent metal cation, and when the metal salt of the fatty acid is a polyvalent metal salt, which is divalent or higher, it has a structure in which fatty acid carboxylate anions are bound to a metal cation in the number equal to the valence of the metal cation.
[0085] In one embodiment, the hydrophobic particles may be a metal salt of a saturated fatty acid having 12 to 20 carbon atoms. For example, the hydrophobic particles may be one or more metal salts of saturated fatty acids selected from the group consisting of a metal salt of lauric acid having 12 carbon atoms in the molecule, a metal salt of tridecylic acid having 13 carbon atoms in the molecule, a metal salt of myristic acid having 14 carbon atoms in the molecule, a metal salt of pentadecanoic acid having 15 carbon atoms in the molecule, a metal salt of palmitic acid having 16 carbon atoms in the molecule, a metal salt of margaric acid having 17 carbon atoms in the molecule, a metal salt of stearic acid having 18 carbon atoms in the molecule, a metal salt of nonadecylic acid having 19 carbon atoms in the molecule, and a metal salt of arachidic acid having 20 carbon atoms in the molecule.
[0086] Preferably, the metal salt of a fatty acid may be a metal stearate, for example one or more metal salts of stearic acid selected from the group consisting of calcium stearate, magnesium stearate, sodium stearate, zinc stearate and potassium stearate.
[0087] The hydrophobic organic particles may also be one or more hydrophobic polymer particles selected from the group consisting of ethylene polymers, propylene polymers, styrene polymers, butadiene polymers, styrene-butadiene copolymers, alkyl acrylate polymers, alkyl methacrylate polymers, alkyl acrylate-acrylonitrile copolymers, acrylonitrile-butadiene copolymers, acrylonitrile-butadiene-styrene copolymers, acrylonitrile-alkyl acrylate-styrene copolymers, alkyl methacrylate-butadiene-styrene copolymers, and alkyl acrylate-alkyl methacrylate copolymers.
[0088] In addition, the hydrophobic particles may be contained in the aqueous dispersion in an amount of 10 to 70 wt % based on the total weight of the aqueous dispersion. If the content of the hydrophobic particles in the aqueous dispersion is too low or too high, the hydrophobic particles may not be stabilized in dispersion, and may aggregate with each other or settle due to gravity.
[0089] In addition, as the surfactant that plays a role in dispersing the hydrophobic particles in the hydrophobic particle aqueous dispersion, any surfactant known in the art that can stabilize the dispersion of the hydrophobic particles can be used without limitation. For example, the surfactant can be one or more surfactants selected from the group consisting of cationic surfactants, anionic surfactants, amphoteric surfactants, and nonionic surfactants. Preferably, in terms of stabilizing the dispersion of the hydrophobic particles, two or more surfactants can be used. More specifically, in consideration of the form of the hydrophobic particles, for example, the form of a metal salt of a saturated fatty acid, a nonionic surfactant and an anionic surfactant, for example, a nonionic surfactant bonded to a long-chain hydrocarbon having 10 or more carbon atoms and a sulfate-based anionic surfactant can be used together to more effectively disperse such hydrophobic particles in water.
[0090] As an example, the cationic surfactant may include dialkyldimethylammonium salts, alkylbenzylmethylammonium salts, etc.; the anionic surfactant may include alkyl polyoxyethylene sulfates, monoalkyl sulfates, alkylbenzene sulfonates, monoalkyl phosphates, sulfates having a functional group containing a long chain hydrocarbon or a sodium salt thereof, such as sodium lauryl sulfate, sodium dodecyl sulfate, or sodium laureth sulfate; the amphoteric surfactant may include alkyl sulfobetaines, alkyl carboxybetaines, etc.; and the nonionic surfactant may include polyoxyethylene alkyl ethers such as polyethylene glycol, polyoxyalkylene alkylphenyl ethers, polyoxyethylene arylphenyl ethers, fatty acid esters such as sorbitan monopalmitate, fatty acid sorbitan esters, or glycerin monostearate, alkyl monoglyceryl ethers, alkanolamides, alkyl polyglycoside, etc., but is not limited thereto.
[0091] The hydrophobic particle aqueous dispersion may have a pH of 7 or more. If the hydrophobic particle aqueous dispersion has a pH of less than 7, it is not suitable because it becomes acidic and it is difficult to stabilize the hydrophobic particles, which are metal salts of fatty acids.
[0092] Meanwhile, the hydrophobic particles are used in an amount of 0.01 to 0.5 parts by weight based on 100 parts by weight of the acrylic acid monomer. If the content of the hydrophobic particles is too low, the bubble stabilizing effect may be insufficient and the absorption speed may be slow, and if the content of the hydrophobic particles is too high, the amount of surfactant used to stabilize the hydrophobic particles in the hydrophobic particle aqueous dispersion may increase, and the surface tension may be reduced. For example, the hydrophobic particles may be used in an amount of 0.01 or more, 0.03 or more, 0.05 or more, or 0.08 or more, and 0.5 parts by weight or less, 0.4 parts by weight or less, 0.3 parts by weight or less, or 0.2 parts by weight or less based on 100 parts by weight of the acrylic acid monomer.
[0093] In addition, the carbonate-based foaming agent foams during polymerization, forming pores in the hydrous gel polymer to increase the surface area, and one or more types selected from the group consisting of sodium bicarbonate, sodium carbonate, potassium bicarbonate, potassium carbonate, calcium bicarbonate, calcium carbonate, magnesium bicarbonate, and magnesium carbonate can be used.
[0094] The carbonate-based foaming agent can be used in an amount of 0.005 to 1 part by weight based on 100 parts by weight of the acrylic acid-based monomer. If the content of the foaming agent is less than 0.005 parts by weight, the role of the foaming agent may be insignificant, and if the content of the foaming agent is more than 1 part by weight, the pores in the crosslinked polymer are too large, so that the gel strength of the produced superabsorbent resin is reduced and the density is reduced, which may cause problems in distribution and storage. For example, the carbonate-based foaming agent may be 0.01 parts by weight or more, 0.05 parts by weight or more, and 0.5 parts by weight or less, 0.3 parts by weight or less, or 0.2 parts by weight or less based on 100 parts by weight of the acrylic acid-based monomer.
[0095] In addition, the carbonate foaming agent and the hydrophobic particles can be used in a weight ratio of 1:0.1 to 1:2. If the hydrophobic particles are used in an amount that is too low compared to the carbonate foaming agent, it is difficult to effectively capture the generated bubbles, and if the hydrophobic particles are used in an amount that is too high compared to the foaming agent, various physical properties such as water retention and absorption speed may be reduced. Specifically, the carbonate foaming agent and the hydrophobic particles can be used in a weight ratio of 1:0.4 or more, 1:0.6 or more, or 1:0.8 or more, and 1:1.7 or less, 1:1.5 or less, or 1:1.2 or less. As an example, the carbonate foaming agent and the hydrophobic particles can be used in a weight ratio of 1:1.
[0096] Meanwhile, a bubble generator can be used instead of the foaming agent. As such a bubble generator, any microbubble generator that has been used for foaming a monomer composition in a process for producing a superabsorbent resin can be used without any special restrictions. One example of such a microbubble generator is a device that passes the monomer composition through a tubular flow path having a plurality of protruding pins attached therein at a predetermined supply speed, for example, 50 to 1500 (L / min), and causes the monomer composition to collide with the protruding pins to foam. One example of such a microbubble generator is disclosed in Korean Patent Publication No. 2020-0128969, and it is of course possible to obtain and apply the commercial products applied in the examples described below.
[0097] Preferably, the adhesive may be applied evenly or randomly without any particular pattern.
[0098] The adhesive may be applied by a number of methods known to those skilled in the art. For example, the adhesive may be sprayed, rolled, or spun onto the surface of the nonwoven fabric or superabsorbent polymer. The type of adhesive is not particularly limited as long as it is an adhesive that is generally used in absorbents. For example, the adhesive may be hydrophilic, hydrophobic, biodegradable, bioinducible, or a combination thereof. Preferably, the superabsorbent polymer layer and the nonwoven fabric are continuously present without any bond sites separated between them when the adhesive is applied. When the absorbent has separate bond sites, bond sites such as lattices are formed on a woven fabric such as a nonwoven fabric by ultrasonic bonding, and the superabsorbent polymer is filled between the bond sites and fixed. Although this method of fixing the superabsorbent polymer can improve the fixation rate of the superabsorbent polymer, it may have the disadvantage that the superabsorbent polymer can move between the bond sites, resulting in a poor filling rate.
[0099] On the other hand, preferably, 350 cm 2 The amount of adhesive (product name: FLC7228AZP, manufacturer: HB Fuller) applied to the nonwoven fabric is 0.3 to 3 g per application, and the total amount applied may vary depending on the number of applications. 2 The total amount of adhesive (product name: FLC7228AZP, manufacturer: HB Fuller) applied onto the nonwoven fabric may be 0.3 to 10 g.
[0100] On the other hand, the absorbent body A first step of applying an adhesive and a superabsorbent polymer to a first nonwoven fabric at least twice to form a superabsorbent polymer layer; A second step of applying an adhesive onto the superabsorbent polymer; and a third step of attaching and sealing a second nonwoven fabric onto the first nonwoven fabric after the second step has been completed.
[0101] The coating, adhering and sealing methods in each of the above manufacturing steps may be performed by a number of methods known to those skilled in the art, and are not particularly limited as long as they are commonly used methods.
[0102] sanitary products Meanwhile, according to another embodiment of the present invention, a sanitary product including the absorbent body of the above-mentioned embodiment is provided. Such a sanitary product may include, for example, the absorbent body, a liquid-permeable upper sheet formed on the upper part of the absorbent body (e.g., in the direction that contacts the user's skin), and a waterproof back sheet formed on the lower part of the absorbent body (e.g., in the direction opposite to the direction that contacts the user's skin).
[0103] In the construction of such a sanitary product, the liquid-permeable top sheet may comprise a material that is generally soft to the touch and does not irritate the skin of the user. In addition, the top sheet suitably comprises a material that allows liquid body secretions, such as urine, to pass quickly through to the absorbent. With this in mind, the top sheet may be made of a wide range of materials, such as a porous resin film, natural fibers, synthetic fibers, or a mixture of natural and synthetic fibers.
[0104] In addition, the waterproof backsheet must be impermeable to liquids and therefore must exhibit the property of preventing bodily secretions absorbed and contained in the absorbent from soiling products that come into contact with sanitary products such as the user's clothes, bedsheets, etc. In consideration of this, the backsheet suitably includes a material that is impermeable to liquids and permeable to gases, and may include, for example, a resin film or a material to which a nonwoven fabric is further attached.
[0105] The sanitary product described above can have a slim and thin structure without fluff pulp by including the absorbent body of an embodiment, and the unit price can also be reduced. In addition, the movement of the superabsorbent polymer particles in the absorbent layer and the sanitary product is effectively suppressed by the porous nonwoven fabric layer, so that the sanitary product can exhibit more uniform performance and can maintain an appropriate shape even after absorbing a large amount of water. In addition, the deterioration of the physical properties of the superabsorbent polymer particles due to a large amount of adhesive, etc. can be suppressed, and excellent absorption performance, etc. can be maintained.
[0106] Such a sanitary product may be any personal sanitary product, such as a diaper, a sanitary napkin or an incontinence pad, and may have, apart from the aforementioned configurations, the usual configurations for each type of sanitary product.
[0107] The present invention will be described in more detail below for a better understanding of the present invention. However, the following examples are merely illustrative of the present invention, and the content of the present invention is not limited to the following examples.
[0108] Production Example 1: Production of hydrophobic silica aqueous dispersion 100g of water was put into a high shear mixer, and then, while stirring at 5000 rpm, hydrophobic silica having an average particle size of 0.3 μm and a contact angle with water of 130° and hydrophobic silica having an average particle size of 3 μm and a contact angle with water of 130° were dispersed at 0.2 wt% and 2 wt%, respectively, based on the total weight of the final aqueous dispersion, and gradually added. When the silica was completely added, the mixture was stirred at 8000 rpm at a temperature of 45° C. for 30 minutes. At this time, the pH of the obtained hydrophobic silica aqueous dispersion was 9.
[0109] Production Example 2: Production of superabsorbent resin (Step 1) 100 parts by weight of acrylic acid was mixed with 0.01 parts by weight of PEGDA 400 (polyethylene glycol diacrylate 400) as an internal crosslinking agent and 0.1 parts by weight of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide as a photoinitiator to prepare a monomer solution. Then, the monomer solution was continuously fed to a metering pump, and 160 parts by weight of 24% by weight of sodium hydroxide aqueous solution was continuously added at the same time, and 3 parts by weight of 4% by weight of sodium persulfate aqueous solution, 5 parts by weight of 4% by weight of ethylene glycol diglycidyl ether (EJ1030s), 5 parts by weight of 4% by weight of sodium bicarbonate aqueous solution, 0.2% by weight of hydrophobic silica having an average particle size of 0.3 μm prepared in Preparation Example 1, and 5 parts by weight of hydrophobic silica aqueous dispersion containing 2% by weight of hydrophobic silica having an average particle size of 3 μm were mixed at high speed to prepare a monomer composition. Through this transfer, the monomer composition was fed into a polymerization reactor consisting of a moving conveyor belt, and UV polymerization was carried out for 3 minutes by irradiating ultraviolet rays through a UV irradiation device to produce a sheet-shaped hydrogel polymer.
[0110] (Step 2) The hydrogel polymer was cut into pieces with an average size of about 300 mm or less, and then the pieces were fed into a crusher (equipped with a perforated plate containing a plurality of holes with a diameter of 15 mm) to cut the hydrogel. The crushed hydrogel was then dried in a dryer capable of changing the air direction up and down. Hot air at 180°C was blown in to uniformly dry the hydrogel so that the moisture content of the dried powder was about 5% or less.
[0111] (Step 3) The dried resin was pulverized in a pulverizer and then classified to obtain a base resin with a size of 150 to 850 μm. The pulverizer used was a PULVERISETTE 19 manufactured by FRITSCH. A 12 mm sieve cassette was installed in the pulverizer to perform primary pulverization of the dried hydrogel. Among the following sieves (WS Tylor, 8" STAINLESS-STAINLESS TEST SIEVE), mesh numbers 24 / 32 / 48 / 100 / pan were installed in order, and the pulverized particles were placed in the upper row of the #24 mesh, fixed to the sieve shaker, and classified at 1.5 amplitude for 10 minutes.
[0112] [Table 1]
[0113] After classification was completed, the resin content in the upper part of the #24 mesh was measured, and it was found that the particles contained more than 50% by weight of the dried hydrogel that had been added.
[0114] The particles in the upper row of #24 mesh were subjected to secondary crushing, in which a 1.0 mm sieve cassette was installed in the crusher to crush the dried hydrogel. Sieves (WS Tylor, 8" STAINLESS-STAINLESS TEST SIEVE) with mesh numbers 20 / 32 / 48 / 100 / pan were installed in that order, and the secondary crushed particles were placed in the upper row of #20 mesh, fixed to the sieve shaker, and classified at 1.5 amplitude for 10 minutes.
[0115] The particle weight after classification can be calculated as follows:
[0116] Particle size distribution by particle size = {(sieve weight + dried mass after classification) - (empty sieve weight)} / (dried mass after crushing) x 100
[0117] (Step 4) 100 parts by weight of the base resin powder obtained by classification was sprayed with 8 parts by weight of a surface crosslinking agent aqueous solution containing 1.2 parts by weight of ethylene carbonate, 0.5 parts by weight of propylene carbonate, 0.5 parts by weight of propylene glycol, and 0.5 parts by weight of hydrophilic water-dispersed silica (snotex), and the mixture was stirred at room temperature to mix so that the surface crosslinking liquid was evenly distributed on the base resin powder. Next, the base resin powder mixed with the surface crosslinking liquid was placed in a surface crosslinking reactor to carry out a surface crosslinking reaction.
[0118] In the surface crosslinking reactor, the base resin powder was gradually heated from an initial temperature of about 80°C, and was operated so as to reach a maximum reaction temperature of 190°C after 30 minutes. After reaching the maximum reaction temperature, the reaction was continued for an additional 15 minutes, and then a final superabsorbent resin sample was taken. After the surface crosslinking process, the superabsorbent resin of Example 1 having a particle size of 150 μm to 850 μm was produced by classifying the particles using a standard mesh sieve according to the ASTM standard.
[0119] Experimental Example 1 The physical properties of the superabsorbent polymer produced in Production Example 2 were evaluated by the following methods and are shown in Table 1. Unless otherwise indicated, all of the following physical property evaluations were performed at room temperature (23±1°C) and a relative humidity of 45±1%, and saline or salt water refers to a 0.9 wt% sodium chloride (NaCl) aqueous solution, and salt water at a temperature of 23±1°C was used.
[0120] (1) Bulk density (g / ml): Measures particles with diameters of 150 to 850 μm Approximately 100 g of the superabsorbent resin of each of the Examples and Comparative Examples was placed in a funnel-shaped bulk density measuring device and poured into a 100 ml container, and the weight of the superabsorbent resin in the container was measured. The bulk density was calculated by (weight of superabsorbent resin) / (container volume, 100 ml).
[0121] Bulk density measurements were performed according to EDANA NWSP 251.0.R2(15) method.
[0122] The density cup used was made of a cylindrical stainless steel material, had a capacity (ISO / TR 15510) of (100.0±0.5 ml), an inner diameter of 45.0±0.1 mm, and an inner height of 63.1±0.1 mm.
[0123] The funnel was made of stainless steel and its detailed design conformed to ISO / TR 15510. a) It had the following dimensions: Orifice internal diameter (10.00±0.01) mm, Inclination angle of cone generatrix 20°, Height (145.0±0.5 mm).
[0124] Bulk density analysis was performed at (23±2° C.) and (45±15)% relative humidity.
[0125] First, a density cup was placed under the funnel, and 100g of SAP was filled into the funnel with the orifice closed. A timer was started while the orifice was open, and the time it took for all the SAP to fall out of the funnel was measured. The SAP that overflowed from the density cup was removed and then weighed (W2). The weight of the empty density cup (W1) was measured, and the difference between the two weights was calculated to determine the weight of the SAP in the density cup.
[0126] Bulk density (ρ, g / ml) was calculated as “ρ = (W2-W1) / 100”, where 100 (ml) is the volume of the density cup.
[0127] (2) Water-soluble components measured after swelling for 16 hours (16hr EC,%): Particles with a diameter of 150 to 850 μm were measured. The water-soluble components in the above examples and comparative examples were measured according to the method of EDANA NWSP 270.0.R2(15).
[0128] (3) Centrifuge Retention Capacity (CRC, g / g): Measures particles with a diameter of 150 to 850 μm The water retention capacity of each resin was measured by its absorbency under no load according to EDANA NWSP 241.0.R2(15).
[0129] Specifically, the highly water-absorbent resin W0(g) (approximately 0.2g) was evenly placed in a nonwoven envelope, sealed, and then immersed in physiological saline (0.9% by weight) at room temperature. After 30 minutes, the envelope was evacuated for 3 minutes at 250G using a centrifuge to remove water, and the weight of the envelope W2(g) was measured. The same procedure was also carried out without using the resin, and the weight W1(g) at that time was measured. The CRC(g / g) was calculated using the weights obtained according to the following formula:
[0130] [Mathematical formula 1] CRC(g / g)={[W2(g)-W1(g)] / W0(g)}-1
[0131] (3) Absorbency under pressure (0.7AUP: Absorbtion Under Pressure, g / g): Measures particles with a diameter of 150 to 850 μm The 0.7 psi pressure absorbency of each resin was measured according to EDANA NWSP 242.0.R2(15).
[0132] Specifically, a 400 mesh stainless steel iron net was attached to the bottom of a plastic cylinder with an inner diameter of 60 mm. Under conditions of room temperature and 50% humidity, superabsorbent resin W0(g) (0.90 g) was evenly spread on the iron net, and a piston capable of applying a uniform load of 0.3 psi was placed on top of it. The piston had an outer diameter slightly smaller than 60 mm, and there was no gap between it and the inner wall of the cylinder, so that its up and down movement was not hindered. At this point, the weight W3(g) of the device was measured.
[0133] A glass filter with a diameter of 90 mm and a thickness of 5 mm was placed inside a petroleum dish with a diameter of 150 mm, and physiological saline composed of 0.9% by weight sodium chloride was poured so that it was flush with the top surface of the glass filter. A sheet of filter paper with a diameter of 90 mm was placed on top of the physiological saline. The measuring device was placed on the filter paper, and the liquid was absorbed under a load for one hour. After one hour, the measuring device was lifted and its weight W4 (g) was measured.
[0134] Using the obtained weights, the pressurized absorbency (g / g) was calculated according to the following formula.
[0135] [Mathematical formula 2] AUP(g / g)=[W4(g)-W3(g)] / W0(g)
[0136] (4) Absorption rate (Vortex time, s): Measures particles with diameters of 150 to 850 μm The absorption speed (vortex time) of the superabsorbent resins of the above Examples and Comparative Examples was measured by the following method.
[0137] (i) First, 50 mL of 0.9% salt water was poured into a 100 mL beaker with a flat bottom using a 100 mL mass cylinder. (ii) Next, the beaker was placed so that it was positioned at the center of a magnetic stirrer, and then a circular magnetic bar (diameter 30 mm) was placed in the beaker. (iii) Then, the stirrer was operated so that the magnetic bar was stirring at 600 rpm, and the lowest point of the vortex generated by the stirring was placed on the magnetic bar. (iv) After confirming that the temperature of the salt water in the beaker had reached 24.0°C, 2±0.01 g of the superabsorbent polymer sample was added while simultaneously starting a stopwatch. The time until the vortex disappeared and the liquid surface became completely horizontal was measured in seconds, and this was regarded as the absorption rate.
[0138] [Table 2]
[0139] Example 1 On a first nonwoven fabric (product name: Softhann (registered trademark), manufacturer: Sambo) 1 having a size of 350 mm x 100 mm, 0.4 g of adhesive (product name: FLC7228AZP, manufacturer: HB Fuller) (adhesive layer, 3) was uniformly applied using a hot melt sprayer, and then 4 g of the superabsorbent resin prepared in the above preparation example was uniformly applied at a feed rate of 2 g / s to prepare a first coating layer 4 of superabsorbent resin. 0.4 g of adhesive was applied thereon to prepare a first coating layer 5 of adhesive. Then, the manufacturing process of the first coating layer 4 of superabsorbent resin and the first coating layer 5 of adhesive was repeated two more times to prepare a second coating layer 6 of superabsorbent resin, a second coating layer 7 of adhesive, a third coating layer 8 of superabsorbent resin, and an adhesive layer 4, and then a second nonwoven fabric (product name: Softhann (registered trademark), manufacturer: Sambo) 2 was attached to prepare an absorbent. The amount of adhesive used in each adhesive layer was the same at 0.4 g, and the amount of superabsorbent resin used in each superabsorbent resin layer was the same at 4 g.
[0140] Example 2 An absorbent body was produced in the same manner as in Example 1, except that 0.8 g of each adhesive was applied.
[0141] Example 3 An absorbent body was produced in the same manner as in Example 1, except that 1.6 g of each adhesive was applied.
[0142] Comparative Example 1 0.6g of adhesive (product name: FLC7228AZP, manufacturer: HB Fuller) (adhesive layer) was uniformly applied using a hot melt sprayer onto a first nonwoven fabric (product name: Softhann (registered trademark), manufacturer: Sambo) measuring 350mm x 100mm, and then 12g of the superabsorbent resin prepared in the above Preparation Example was uniformly applied at a feed rate of 2g / s to prepare a superabsorbent resin coating layer. 0.6g of adhesive was then uniformly applied onto the first nonwoven fabric to prepare an adhesive layer, and a second nonwoven fabric (product name: Softhann (registered trademark), manufacturer: Sambo) was attached to prepare an absorbent.
[0143] Comparative Example 2 12 g of the superabsorbent resin prepared in the above Preparation Example was applied to a first nonwoven fabric (product name: Softhann (registered trademark), manufacturer: Sambo) measuring 350 mm x 100 mm, and then heat was applied at a temperature of 100°C to 150°C for 10 to 30 seconds using a thermal bonder (product name: SK110, manufacturer: LOVERO) to fix the superabsorbent resin in a lattice form through thermal bonding, thereby producing an absorbent body.
[0144] Experimental Example 2 The physical properties of the absorbents produced in the above Examples and Comparative Examples were evaluated by the following methods, and are shown in Table 2 below.
[0145] (1) Fixation rate of the superabsorbent resin layer in the absorbent body (% by weight) The fixation rate of the superabsorbent polymer layer in the nonwoven fabric was determined by testing the amount of superabsorbent polymer in the core of the nonwoven fabric that leaked out. The absorbent bodies of the above examples and comparative examples were subjected to vibration at a frequency of 65 times / min and an amplitude of 15 mm for 100 vibrations, and the amount of superabsorbent polymer remaining in the absorbent body without leakage was measured and expressed as weight percent.
[0146] (2) Super absorbent resin filling rate (%) The superabsorbent resin filling rate means the area ratio of the superabsorbent resin in the absorbent body, and is measured as follows.
[0147] The absorbent was dyed with a dye (product name: FD&C BLUE NO.1 POWDER, manufacturer: SENSIENT) and then dried. After confirming that only the superabsorbent resin portion was selectively dyed, the area of the dyed portion was measured with a color meter (device name: Labscan XE, manufacturer: Hunter lab) under the conditions of a spectral range of 400nm to 700nm and a wavelength resolution of <3nm.
[0148] (3) Rewet (g) In order to evaluate the rewetting property under pressure conditions, the rewetting property was measured by the following method.
[0149] Two minutes after injecting 85 mL of 0.9 wt % sodium chloride aqueous solution (physiological saline) into the center of the absorbent (350 mm x 100 mm x 3 mm in size) prepared by the above method, a piece of paper (300 gsm filter paper (S-300, HANKUK PAPER), approximately 1.5 g (W6 (g)) per sheet) measuring 300 mm x 90 mm in size was placed in the center of the absorbent. Two minutes later, the weight (W5 (g)) of the paper was measured to measure the amount of salt water seeping out of the absorbent and the paper was removed. 15 minutes after the injection of the physiological saline, a weight was placed in the center of the absorbent and a pressure of 0.42 psi was applied, while another 85 mL of physiological saline was injected into the same position. After 15 minutes, the weight placed on the absorbent was temporarily removed and new paper (300 gsm filter paper (S-300, HANKUK PAPER), approximately 1.5 g (W6(g)) per sheet) was placed on the absorbent, and then the weight was placed on the paper again to position the paper between the absorbent and the weight. After 2 minutes, the weight (W7(g)) of the paper was measured and the amount of salt water that had seeped out of the absorbent into the paper was measured, and the rewet amount (g) was calculated according to the following mathematical formula 3.
[0150] [Mathematical formula 3] Rewetting amount (g)=(W5(g)-W6(g))+(W7(g)-W6(g))
[0151] In the above mathematical formula 3, W5(g) is the weight of the paper that absorbs the liquid that seeps out from the absorbent body for 2 minutes 2 minutes after saline solution is injected into the absorbent body under no pressure, W6(g) is the initial weight of the paper, and W7(g) is the weight of the paper that absorbs the liquid that seeps out from the absorbent sheet for 2 minutes under a load (0.42 psi) after saline solution is injected into the absorbent sheet under no pressure and under pressure.
[0152] [Table 3] [Explanation of symbols]
[0153] 1: 1st nonwoven fabric 2:Second nonwoven fabric 3: Adhesive layer 4: First coating layer of superabsorbent resin 5: First layer of adhesive 6: Second coating layer of highly absorbent resin 7: Second layer of adhesive applied 8: Third coating layer of highly absorbent resin 9: Adhesive layer
Claims
1. A first nonwoven fabric; A second nonwoven fabric; A superabsorbent polymer layer is provided between the first and second nonwoven fabrics, The superabsorbent polymer layer includes a superabsorbent polymer and an adhesive, The superabsorbent polymer layer is bonded to the first and second nonwoven fabrics using an adhesive and does not contain pulp. The following (1) and (2) are satisfied: Absorber. (1) The absorbent body is subjected to a vibration frequency of 65 times / min, an amplitude of 15 mm, and 100 times vibration, and the fixation rate, which is measured by measuring the amount of the superabsorbent polymer remaining in the absorbent body without leakage, is 90% or more; (2) The absorbent body is dyed with a dye and then dried. After confirming that only the highly absorbent resin portion is selectively dyed, the area of the dyed portion is measured with a color meter to find that the filling rate is 90% or more.
2. The superabsorbent resin layer is formed by alternately applying a superabsorbent resin and an adhesive two or more times. The absorbent body according to claim 1.
3. The superabsorbent resin layer is formed by sequentially laminating a first coating layer of a superabsorbent resin, a first coating layer of an adhesive, a second coating layer of a superabsorbent resin, a second coating layer of an adhesive, and a third coating layer of a superabsorbent resin. The absorbent body according to claim 1.
4. The thickness of the superabsorbent resin layer is 5 mm or less. The absorbent body according to claim 1.
5. The highly water-absorbent resin layer has a surface area per unit area (m 2 ) containing 100 g or more of a superabsorbent resin; The absorbent body according to claim 1.
6. The superabsorbent resin is a base resin including a crosslinked polymer of an acrylic acid monomer and an internal crosslinking agent, the base resin including an acidic group, at least a portion of which has been neutralized; A superabsorbent resin comprising a surface cross-linked layer formed on the base resin and in which the cross-linked polymer is additionally cross-linked via a surface cross-linking agent, Satisfy the following 1) to 4); The absorbent body according to claim 1. 1) A water retention capacity (CRC) of 32 g / g to 40 g / g as measured by EDANA NWSP 241.0.R2 (15); 2) The water-soluble component after swelling for 16 hours as measured by EDANA NWSP 270.0.R2 (15) is 10% by weight or less; 3) The absorption rate by the vortex method (vortex time) is 30 seconds or less; 4) A bulk density of 0.50 g / ml or more and 0.65 g / ml or less, as measured by EDANA NWSP 251.0.R2(15).
7. The rewet value of the absorbent is 3 g or less. The absorbent body according to claim 1.
8. The adhesive is applied without a pattern. The absorbent body according to claim 1.
9. The absorbent body is A first step of applying an adhesive and a superabsorbent polymer to a first nonwoven fabric two or more times to form a superabsorbent polymer layer; A second step of applying an adhesive onto the superabsorbent polymer; and a third step of attaching and sealing a second nonwoven fabric onto the first nonwoven fabric after the second step is completed. The absorbent body according to claim 1.
10. A sanitary article comprising an absorbent body according to any one of claims 1 to 9.
11. 11. The sanitary article of claim 10, comprising the absorbent body, a liquid-permeable topsheet formed on top of the absorbent body, and a waterproof backsheet formed on a bottom of the absorbent body.
12. 11. The hygiene article according to claim 10, which is a diaper, a sanitary napkin or an incontinence pad.
Citation Information
Patent Citations
Absorbent Sheet Composition
CN102281852A
Body liquid absorbing article
JP2007143677A
Absorber and absorbent article comprising the same
JP2015100611A
Absorber and absorbent article comprising the same
JP2015100612A
Absorber and absorbent article including the same
JP2018166887A